Sosialisasi dan Pendampingan Pembentukan Koperasi Syariah pada Kelompok Penjahit Sakinah Kota Bengkulu - Khairul Bahrun; Amir Mukadar; Hesti Setiorini; Marini Marini (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity was carried out among the members of the Sakinah Tailors' social gathering in the Kampung Bali sub-district of Sungai Serut, Bengkulu City. The members of the Sakinah Tailors' social gathering have the potential to grow because the members or partners already have sewing skills or their own sewing businesses. This is a supporting factor in developing a cooperative. However, they are constrained by limited knowledge about the procedures for forming a cooperative, capital, and how to prepare cooperative financial reports. So far, the members of the Penjahit Sakinah sewing circle have been carrying out savings and loan activities, but the administrators still carry out savings and loan activities in a conventional manner, so they want to form a sharia savings and loan cooperative. Therefore, the Community Service Team from the Faculty of Economics and Business wants to conduct socialization and assistance activities for the formation of a sharia-based savings and loan cooperative. The method used is through direct socialization and assistance activities using the Excel application, followed by posting, adjusting journals, and reporting activities.